Protective effect of dried latex and alkaloid fraction of Croton palanostigma against gastric mucosal injury induced by ethanol in rats - Ayala Pío, Salomón (2001)
OBJECTIVE: The gastric protective abilities of dried sap and alkaloid fraction of Croton palanostigma and sucralfate against ethanol-induced necrosis was compared by means of standard experimental rat model. Subchronic toxicity was determined. MATERIAL AND METHODS: A pretreatment with either saline solution, dried sap of C. palanostigma 120 mg/kg, alkaloid fraction of C. palanostigma 20 mg/kg, 35 mg/kg y 50 mg/kg or sucralfate was given to 60 rats. Intragastric administration of 2 mL of 100% ethanol was accomplished one hour later. A gastrectomy was perfomed four hours later followed by macroscopic and histological evaluation of the gastric lesions. Subchronic toxicity was determined with doses of 0,12, 0,40 and 1,20 mL/kg of sap for a 30-day period with biochemical and histopathologic study of the organs. RESULTS: Pretreatment with dried sap and alkaloid fractions of C. palanostigma and sucralfate resulted in a significant reduction of ethanol-induced gastric mucosa necrosis. Subchronic toxicity with C. palanostigma largest dose showed risk of liver steatosis. CONCLUSION: In the present study, dried sap and alkaloid fraction of C. palanostigma and sucralfate showed a significative protective effect, being potentially useful as a therapeutic tool. Subchronic toxicity in higher doses showed risk of liver steatosis.